Event classification and optimization methods using artificial intelligence and other relevant techniques: Sharing the experiences - Mohamed A.A.; Hasan A.B.; Ghazali A.B.M. (American Institute of Physics Inc., 2023)
Classification of large data into respected classes or groups could be carried out with the help of artificial intelligence (AI) tools readily available in the market. To get the optimum or best results, optimization tool could be applied on those data. Classification and optimization have been used by researchers throughout their works, and the outcomes were very encouraging indeed. Here, the authors are trying to share what they have experienced in three different areas of applied research.